THE USE OF ROUND TABLE TECHNIQUE FOR TEACHING READING COMPREHENSION TO THE EIGHTH GRADE STUDENTS - ardayati ardayati; Maria Ramasari (STKIP PGRI Lubuklinggau, 2022)
The problem of this study was “was significantly effective to teach reading comprehension by using Round Table Technique to the eighth students?” Therefore, the aim of this study was to find out whether or not it was effective to teach reading comprehension by using Round Table Technique to the eighth grade students. The pre–experimental was applied in this study with one group pre-test and post-test design. The population in this study was all the eighth grade students of SMP Negeri 5 Lubuklinggau that consisted of 181 students. The sample 26 was taken through cluster random sampling. There were analyzed through four technique; (1) individual score, (2) Conversional of individual score based on Minimum Mastery Criteria (MMC), (3) Normality Testing, and (4) Matched t-test. The result of this study were (1) the average score in pre-test was 44.46 (2) the average score in the post-test was 75.38 and the result matched t-test was 10.287 , which higher than 1,708 t-table. The critical value of 95% with degree of freedom (df) = 25 (26-1) significant level was 0.05. Therefore, the null hypothesis (Ho) was rejected and alternative (Ha) was accepted. It was means that it is effective to teach reading comprehension by using Round Table Technique to the eighth grade students.